APIP Capabilities, SPIP Maturity, Audit Opinions, and Follow-Up on Audit Recommendations for Corruption Prevention - Asrul Hidayatul; Muhammad Din; Muhammad Ikbal Abdullah; Fikry Karim (SAFE-Network, 2026)
This study aims to analyze the influence of the capabilities of the Government Internal Supervisory Apparatus (APIP), the maturity of the Government Internal Control System (SPIP), audit opinions, and follow-up on audit recommendations on the prevention of corruption in local governments in Indonesia. The method used is quantitative with purposive sampling techniques in 442 district and city local governments during the 2019-2023 period. The results show that APIP capabilities and SPIP maturity have a significant positive effect on corruption prevention, meaning that improving APIP capabilities and SPIP maturity can strengthen the oversight system and increase the effectiveness of corruption prevention. On the other hand, although audit opinions have a positive impact on transparency, their effect on corruption prevention is not proven to be significant. This shows that audit opinions alone are not sufficient to prevent corruption without concrete follow-up. This study also found that follow-up on audit recommendations has a significant effect on improving the quality of financial reports and reducing the potential for corruption. Therefore, this study suggests that local governments should focus more on strengthening APIP capabilities, implementing a more mature SPIP throughout the region, and ensuring effective follow-up on audit recommendations. This step is expected to strengthen corruption prevention, increase accountability, and improve transparency in regional financial management. This study contributes to improving cleaner and more accountable governance.